Novel multicomponent magnesium alloys: High strength-elongation synergy and PEO-driven corrosion resistance - K Renuga Devi; Dondapati Sreekanth (Results in Engineering)
This study investigates the innovative approach of utilizing multiple alloying elements at micro-alloying levels to enhance solution strengthening and their contrasting behaviour in higher compositions leading to intermetallic formation. Two magnesium-based alloys were developed: a high entropy alloy (HEA) Mg82(CaMnZn)15Sn2(AgCeSr)1 (at.%) and a micro-alloy (MA) Mg-0.1Ag-0.15Ca-0.2Ce-0.1Mn-0.1Sn-0.2Sr-0.5Zn (wt.%). The micro-alloy demonstrated exceptional mechanical performance, achieving a tensile strength of 203 MPa and an impressive elongation to failure of 21 %, underscoring its potential for load-bearing applications. To enhance surface properties and corrosion resistance, plasma electrolytic oxidation (PEO) treatment was applied, resulting in significantly improved surface hardness and corrosion resistance. Notably, the PEO-treated micro-alloy achieved a corrosion current density (icorr) of 1.24 × 10⁻⁸ A/cm² in simulated body fluid (SBF), indicative of its superior degradation resistance. Bioactivity evaluations further revealed a stable pH profile and a near-stoichiometric Ca/P ratio of 1.66 on the PEO-coated micro-alloy surface, confirming its enhanced osteoconductivity and potential for biomedical applications. This work establishes a foundation for advancing magnesium-based alloys tailored for orthopaedic implants and other biomedical devices.